Unveiling the Art and Science of Investment and Financing Decision Making - Ibrahim, Fifi Nurafifah (Advances in Management & Financial Reporting, 2024)
Purpose: This study explores the intricate dynamics of investment and financing decision-making, emphasizing the integration of qualitative judgment and quantitative analysis. The research investigates the foundational theories, empirical findings, and practical implications that shape these decisions, highlighting their significance in financial management and economic activities. Research Design and Methodology: The research employs a comprehensive literature review methodology, systematically analyzing existing scholarly works to identify themes, patterns, and relationships within the literature. This approach involves identifying relevant sources through extensive search strategies, critically evaluating the quality and relevance of the selected literature and synthesizing key findings and theoretical insights. Findings and Discussion: The study reveals that a complex interplay of theoretical frameworks and empirical evidence drives investment and financing decisions. The Modigliani-Miller theorem and the efficient market hypothesis provide foundational insights, while behavioral finance highlights cognitive biases that influence decision-making. Empirical findings emphasize the role of firm-specific characteristics and market conditions in shaping capital structure choices and investment behavior. Practical considerations, including managerial overconfidence and asymmetric information, further complicate these decisions. Implications: The insights from this research are valuable for practitioners, policymakers, and researchers. Understanding the multifaceted nature of investment and financing decisions can enhance financial management practices, inform regulatory frameworks, and guide future research directions. Integrating theoretical insights with empirical evidence and practical considerations enables stakeholders to navigate the complexities of financial markets, fostering informed decision-making and promoting sustainable economic growth.